Intercropping Farming System and Farmers Income - Muhammad Arsyad; Yusmiati Sabang; Nurariaty Agus; Sitti Bulkis; Yoshio Kawamura (AGRIVITA, Journal of Agricultural Science, 2020)
Agriculture cultivation systems and farmer’s income are the crucial issues in many agriculture-based developing countries. Our previous study proved that the polyculture system positively affects land productivity and land-use efficiency. This research investigated the relationship between intercropping farming systems and farmer’s income. We hypothesized that the intercropping farming system increases farmer’s income compared to monoculture. The farming income analysis was carried out using Microsoft Excel and STATA software. The results showed that the farmer’s income derived from the intercropping farming system differs from monoculture. Based on the T-test, the intercropping farming system provided a higher income. Intercropping farming systems that have higher plant diversity, contributed to higher farmer income from different plant yields. Farmers that applied the intercropping system would harvest of 2-3 different plants from one cultivated land at the same time with regular planting distance. These indicated that the intercropping farming system reduces the risk of loss due to price fluctuations of products and the higher input costs during the production process.